2021
DOI: 10.13107/jocr.2021.v11.i05.2218
|View full text |Cite
|
Sign up to set email alerts
|

Wedge Osteotomy with Tens Nailing in Monostotic Fibrous Dysplasia of Tibia – A Case Report

Abstract: Introduction: Titanium elastic nailing (TENS) with wedge osteotomy for the management of monostotic fibrous dysplasia (FD) of tibia is done in a 6-year-old male patient. Case Report: This is a case describing monostotic FD of right tibia in a 6-year-old male patient. The patient’s parents noticed a diffuse swelling in the right leg a few days after birth. It was managed conservatively till 3 years of age when the patient started complaining of pain in his right leg and difficulty in walking and running. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…After training the data on the model, SVM, KNN and Random Forest algorithm were used to classify the data. Finally, they compared the results of the three models and found that the Random Forest classifier has higher accuracy than other classifiers [7].…”
Section: The Difference Between the Machine Learning And The Deep Lea...mentioning
confidence: 99%
“…After training the data on the model, SVM, KNN and Random Forest algorithm were used to classify the data. Finally, they compared the results of the three models and found that the Random Forest classifier has higher accuracy than other classifiers [7].…”
Section: The Difference Between the Machine Learning And The Deep Lea...mentioning
confidence: 99%